"Had there been a Monica in each subject, I would have liked going to school every day": a study of students' perceptions of what characterizes excellent teachers and their teaching actions. Issue 1 (2nd January 2021) - Hirsh, Åsa; Segolsson, Mikael
ABSTRACT: The current study – guided by the overarching research question What aspects of successful teaching unfold in students' descriptions of the teachers that they perceive as being really good teachers? – is situated within a larger research project aimed at extending knowledge about successful teaching and teachers. It builds on 20 focus-group interviews with 102 students aged 16–18 in ten Swedish municipalities. Based on inductive qualitative content analysis carried out on manifest data level, eight aspects unfold that – from a student perspective – characterise excellent teachers and teaching. These are subsequently problematised from an opportunity-to-learn (OTL) perspective, and in relation to various theoretical understandings of what successful teaching encompasses. It is concluded that such teaching that students perceive as leading to knowledge-development and well-being is characterised by aspects that can be understood – in various ways – as relational, i.e. as unfolding through participative communication in the interplay and interaction that constitute the space between teacher and students. Throughout students' descriptions it is also obvious that the teachers they perceive as the best are scaffolders and shepherds who manage to balance between simultaneously scaffolding and challenging students cognitively while paying attention to affective dimensions in order to safeguard their social development, self-confidence and self-esteem.